EFFECT OF VARIOUS DIETARY SEAWEEDS ON THE GROWTH OF GOLD-MOUTH TURBAN (Turbo chrysostomus L., 1758) AT LOMBOK, INDONESIA - Ridwanudin, Asep; Firdaus, Muhammad; Pratama, Idham Sumarto; Dwiono, Sigit Anggoro Putro (Marine Research in Indonesia, 2016)
Gold-mouth turban (Turbo chrysostomus L., 1758) is an important source of protein for coastal people in Lombok, West Nusa Tenggara, Indonesia. In order to acquire its seed production technique, research on the culture of the species was carried out since 2012. Feed source is a key concern when culturing animal, including turban snail. Growth of gold-mouth turban fed with seaweed Gracilaria sp., Ulva spp., and Kappaphycus alvarezii was evaluated. Each diet was randomly assigned to triplicate groups of 30 snail juveniles with an initial body weight and shell length of 4.65 Â± 0.00 g and 24.55 Â± 0.08 mm, respectively. After six weeks feeding trial, snails fed with Gracilaria sp. diet had significantly higher (P < 0.05) in final weight, final shell length, weight gain, specific growth rate (SGR) and food intake compared to snails fed with Ulva spp. or K. alvarezii diets.